2021
DOI: 10.53554/boletin.v36i1.330
|View full text |Cite
|
Sign up to set email alerts
|

Varamiento de mega vertebrados marinos en la costa norte de Perú (2017-2018)

Abstract: Los eventos de varamientos de mega vertebrados se están reportando con mayor frecuencia en los últimos años. La costa peruana no es ajena a este tipo de eventos. Diversas limitantes como escaso presupuesto, inaccesibilidad a la zona de ocurrencia y monitoreos discontinuos, imposibilitan investigaciones sistemáticas. A partir del 2014, el Instituto del Mar del Perú (IMARPE) viene realizando monitoreos periódicos de mortandad de fauna marina varada en el litoral norte con el objetivo de caracterizar estos evento… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 52 publications
0
0
0
Order By: Relevance
“…The chordates with the highest number of stranded carcasses in the present study were a mammal (O. flavescens), and three species of birds (S. variegata, P. thagus and P. brasilianus). Our results are consistent with Chauca et al (2021) who recorded data on the stranding of marine mega vertebrates on the north coast of Peru (2017Peru ( -2018, the most abundant species being O. flavescens (50%), S. variegata (14%) and P. thagus (13 %). Among the causes of stranding of carcasses, these authors described a higher percentage of anthropic origin, mainly associated with interaction with fishing activities, demonstrating a conflict between marine vertebrates and fishing boats (Portflitt-thagus -O. flavescens more associated with each other, and the entomofauna of S. variegata determined with the index of presence/absence of Jaccard (Fig.…”
Section: Alpha and Beta Diversity Indicessupporting
confidence: 93%
See 4 more Smart Citations
“…The chordates with the highest number of stranded carcasses in the present study were a mammal (O. flavescens), and three species of birds (S. variegata, P. thagus and P. brasilianus). Our results are consistent with Chauca et al (2021) who recorded data on the stranding of marine mega vertebrates on the north coast of Peru (2017Peru ( -2018, the most abundant species being O. flavescens (50%), S. variegata (14%) and P. thagus (13 %). Among the causes of stranding of carcasses, these authors described a higher percentage of anthropic origin, mainly associated with interaction with fishing activities, demonstrating a conflict between marine vertebrates and fishing boats (Portflitt-thagus -O. flavescens more associated with each other, and the entomofauna of S. variegata determined with the index of presence/absence of Jaccard (Fig.…”
Section: Alpha and Beta Diversity Indicessupporting
confidence: 93%
“…The results of this study show that based on the total number of corpses and the richness of the stranded species, ornithological fauna was more frequently found in comparison to mammals. In regard to corpse number, in their study Chauca et al (2021) reported that the total number of corpses for the northern zone of Peru, specifically for the Regions of Lambayeque (06°22'S-07°10'S), Piura (4°50'S-06°22'S) and Tumbes (3°23'S-4°50'S), was higher for mammals (60.6%) than for birds (39.4%). On the other hand, when evaluated based on species richness, a greater number of birds (n= 19; 67.85%) was observed compared to mammals (n= 9; 32.15%).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations